Integrated Design of Multiscale, Multifunctional Materials and Products - McDowell D. L. David; Panchal J. H. Jitesh; Hae-Jin Choi; Carolyn Conner Seepersad; Allen J. K. Janet; Farrokh Mistree (Amsterdam, Elsevier, 2010)
Заглавие с титульного экрана